PUBLIC RELATIONS STRATEGY OF NORTH SUMATRA REGIONAL POLICE IN IMPROVING POSITIVE IMAGE - Viorella Juliana Ambarita; Muhammad Husni Thamrin (Yayasan Wayan Marwan Pulungan, 2025)
Public Relations in the police is a division or part that is responsible for building and maintaining good relations between the police and the community. This research discusses Public Relations Strategy North Sumatra Regional Police in Improving a Positive Image in the Community. This study uses a descriptive research method with a qualitative approach. Data collection was carried out by interview techniques, observation, documentation, and literature study. The data that has been obtained is analyzed using the theory of Public Relations Strategy by Harwood Childs (2008) which consists of four indicators, namely strategy of publicity, strategy of persuasion, strategy of argumentation, and strategy of image. The results of this study show that Public Relations Strategy The North Sumatra Regional Police in Improving a Positive Image in the Community has fulfilled the theory of Harwood Childs (2008), including: First, publish positive news using online media and media social. Second, carry out an inviting strategy by interacting directly with the community to carry out socialization activities, education, and making a podcast. Third, clarifying or providing a statement of rebuttal in response to a phenomenon or incident that can cause unrest in the community, the steps taken are in the form of Quick Response, Social Media Patrol (Social Media), and inviting journalists/press to clarify the news. Fourth, carrying out actions or activities that can increase public trust based on human interest activities, and conducting morning roll call reports.